The Effect of Using Humanitude Concept by Family Caregivers Care on Depression in Older Persons with Stroke - เปรมทอง, เสาวนีย์; เกศพิชญวัฒนา, จิราพร (Journal of The Royal Thai Army Nurses, 2019)
The study design is quasi-experimental with a pre-posttest control group examining the effect of using the humanitude concept by family caregivers care on depression in older persons with strokes. The humanitude concept 21 was applied to the development of the intervention. The participants were 44 family caregivers of older persons and older persons with post stroke depression who met the inclusion criteria. They were randomly assigned into one experimental group with 22 subjects and a control group with 22 subjects, matched by sex, age, Barthel ADL Index, depression level and relationship of the family caregiver to the older person. The control group received routine nursing care. The experimental group receiving the humanitude concept by family caregiver care was tested for content validity by the experts. The data collecting instrument was the Thai Geriatric Depression Scale (TGDS) with the reliability of 0.93 and the data were analyzed using mean, standard deviation, and t-test. The results showed depression among older persons with strokes after participating using the humanitude concept by family caregiver care were significantly lower than before using the humanitude concept by family caregiver care and lower than the control group, at p .05 level.